Distribution of Zakat Revenues in Pakistan: Some Suggestions and Recommendations for its Reforms = پاکستان میں اموال زکوۃ کی تقسیم اوراس کی اصلاح کے لئے تجاویز - Sayyed Waheed Ahmad; Dr Muhammad Sajjad (Hazara Islamicus, 2018)
Zakat is, out of five, one of the important pillars of Islam. It plays major role in the definition of Islam as stated by the Holy prophet (PBUH) in the famous Hadith Jibreel. Zakat has been mentioned in the Quran with Salat many times. Zakat has spillover effect on a society by helping poor and deprived segment of community in the country. Hence, it is the responsibility of Islamic state to collect Zakat from rich persons and distribute it to the poor ones. In Pakistan the system of Zakat has been implemented since 1980. Collection of Zakat is carried out through banking system. Zakat committees have been constructed or constituted throughout the country. This article discusses the ways and methods of distribution of Zakat and Usher by the said committees. Moreover, this study points out some weaknesses prevailing in the committee system, responsible for the distribution of Zakat and Usher in Pakistan. Finally, some suggestions and recommendations have been furnished which may help to rectify the distribution of Zakat system in Pakistan.